Mapping product and service innovation: A bibliometric analysis and a typology - Klarin, Anton (2019)
Research conducted in the innovation field lags behind organizations’ general technological development and innovativeness. Literature that previously depicted innovation types in developed markets is markedly different from progressively publicized emerging market innovation types. While capital-abundant firms tend to engage in respective pioneering and incremental innovation loops, resource-constrained firms and firms in emerging countries may partially free-ride on existing products and services through innovations such as copycat and frugal. To date, there have been no attempts to holistically consolidate product and service innovation types into one overarching typology. Using novel methods of text mining and co-citation analysis, this study systematically maps three decades of product and service innovation scholarship to provide a typology of eight major product and service innovation types. This is further supported by case study analysis to demonstrate how these innovation types fit into the cost vs market novelty matrix. This study is unique in its methodological proposition to systematically review the innovation scholarship of more than 1,400 articles through comprehensive, quantified, and objective methods that offer transparent and reproducible results. The study provides some clarity regarding the classifications and characteristics of the innovation typology.